Access to surgical care as an efficiency issue: using lean management in French and Australian operating theatres. Issue 5 (27th May 2021) - Mahmoud, Zeyad; Angelé-Halgand, Nathalie; Churruca, Kate; Ellis, Louise A; Braithwaite, Jeffrey
Abstract : Purpose: Millions around the world still cannot access safe, timely and affordable surgery. Considering access as a function of efficiency, this paper examines how the latter can be improved within the context of operating theatres. Carried out in France and Australia, this study reveals different types of waste in operating theatres and a series of successful tactics used to increase efficiency and eliminate wastefulness. Design/methodology/approach: Data for this qualitative study were collected through 48 semi-structured interviews with operating theatre staff in France ( n  = 20) and Australia ( n  = 28). Transcripts were coded using a theory-driven thematic analysis to characterise sources of waste in operating theatres and the tactics used to address them. Findings: The study confirmed the prominence of seven types of waste in operating theatres commonly found in industry and originally identified by Ohno, the initiator of lean: (1) underutilised operating rooms; (2) premature or delayed arrival of patients, staff or equipment; (3) need for large onsite storage areas and inventory costs; (4) unnecessary transportation of equipment; (5) needless staff movements; (6) over-processing and (7) quality defects. The tactics used to address each of these types of waste included multiskilling staff, levelling production and implementing just-in-time principles. Originality/value: The tactics identified in this study have the potential of addressing the chronic and structurally embedded problem of waste plaguing health systems' operating theatres, and thus potentially improve access to surgical care. In a global context of resource scarcity, it is increasingly necessary for hospitals to optimise the ways in which surgery is delivered.